On detection of Gaussian stochactic vectors - M.V. Burnashev (Учёные записки Казанского университета: Серия Физико-математические науки)
The problem of minimax detection of a Gaussian random signal vector in white Gaussian additive noise has been considered. We suppose that an unknown vector s of the signal vector intensities belongs to the given set E. We have investigated when it is possible to replace the set E (and, in particular, by a single point s0) by a smaller set E0 without quality loss.